Efektivitas Uji Tidak Merusak Dan Uji Merusak Pada Dinding Bata Beton Hasil Perbaikan Dengan Additive Kimiawi Di Daerah Rawan Rob - Ludfie Hardian Putra; Erik Kurniawan; Rr. M.I. Retno Susilorini; Budi Santosa (G-SMART, 2018)
This research was conducted by using non-destructive test method and destructive test to investigatethe compressive strength of repaired concrete masonry wall with chemical additive sited at Sriwulan Village which is tidal flooding prone area and PucangGading Village. Non-destructive test using Hammer Test was conducted at age 12 months, 13 months, and 14 months after concrete masonry wall being repaired.It was found that in Sriwulan Village, the highest compressive strength is 49.37 MPa at age 14 month whilethe highest compressive strength value is on the in PucangGading is 50,51 MPa at age 13 month. It was also found that destructive test using Core Drill Test was conducted at age 14 month after the masonry wall have been repaired. The highest compressive strength in Sriwulan village was 58,6 MPa and in PucangGading was 82,63 MPa.